2005
DOI: 10.1002/jbm.b.30393
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behavior of antimicrobial peptide histatin 5 on PMMA

Abstract: Adsorption of antimicrobial peptide histatin 5 on a poly(methyl methacrylate) denture base may serve to prevent biofilm formation, leading to a reduction of denture-induced stomatitis. This study focused on adsorption behavior of histatin 5 onto PMMA surfaces modified using a cold plasma technique and the effectiveness of histatin 5 adsorption for reducing C. albicans biofilm formation by the quartz crystal microbalance-dissipation (QCM-D) technique. PMMA spin-coated specimens were treated with oxygen (O 2 ) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…Many studies have reported that histatin 5 exhibited antimicrobial activity in the treatment of oral fungal infections such as C. albicans (Edgerton et al,1995 ;Kavanagh et al, 2001;Yoshinari et al, 2006). In this study, minTBP1-His 5 exhibited antimicrobial activity against P. gingivalis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Many studies have reported that histatin 5 exhibited antimicrobial activity in the treatment of oral fungal infections such as C. albicans (Edgerton et al,1995 ;Kavanagh et al, 2001;Yoshinari et al, 2006). In this study, minTBP1-His 5 exhibited antimicrobial activity against P. gingivalis.…”
Section: Discussionsupporting
confidence: 54%
“…These antimicrobial activities are believed to regulate biofilm formation in the oral cavity, and have fungicidal and fungistatic effects on Candida albicans cells, in particular (Edgerton et al, 1995;Ruissen et al, 1999). In a previous study, we found that C. albicans colonization on poly(methyl methacrylate) was reduced significantly by adsorption of histatin 5 (Yoshinari et al, 2006). In addition, histatin 5 may play an important role in the regulation of periodontopathic bacteria such as Porphyromonas gingivalis, which is involved in inflammatory periodontal diseases and peri-implantitis (Imatani et al, 2000;Gusman et al, 2001;Kato et al, 2004).…”
mentioning
confidence: 96%
“…The QCM-D method has recently been successfully applied in the field of oral science [12][13][14] . This technique is sometimes used in combination with other methods such as AFM 15) or some optical techniques 14,16) .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro biofilm models have the advantage of lower cost and are ideal for high-throughput screening assays and antifungal testing (12,56,61,71). These models have provided important phenotypic information regarding drug resistance in Candida biofilms.…”
mentioning
confidence: 99%